Back pain persons engaged in rowing - Lewandowski, Andrzej; Piekorz, Zuzanna; Biernat, Katarzyna; Bukowska, Weronika; Radzimińska, Agnieszka; Zukow, Walery (Journal of Education, Health and Sport, 2017)
Introduction: the dynamic and multi-directional development of sport and the relentless pursuit of victory or improve the outcome necessitated increasing workloads. Implementation of the process leads to the expected changes in the morphological structures and motor skills of players and despite the widespread use of wellness, often results in injuries, however, of an overload. Literature, it can be concluded that the problem of overload injuries in rowing sports exists and often affects the lower spine. Thus the objective is to determine the incidence of pain lumbar spine paddlers and their evaluation. Was the hypothesis of the scale of the problem among men and women and its escalation in a group of players with more professional seniority and applying the paddles long. Material and method: the study involved training people Rowing Club RTW Lotto-"Bydgostia" during the start, which are characterized by a relatively high load, which are characterized by a relatively high load. Uses the exclusive survey measured basic morphological and clinical tests, questionnaires, and functional research rated the intensity of pain and degree of loss of movable active lumbar spine. Obtained the test results sets 34 men and 35 women of different ages and progress. It has been developed the basic statistical methods taking into account the diversity of the occurrence of pain in the spine or the lack of their statements, as well as training experience and type of used oars. Statistic; Uses the test Shapiro-Wolf, t-Student, Kruskal-Walis and Pearson Chi square, and to the assessment of the traineeship training and clinical test results, test the correlation of Spearman. Statistical analysis was performed on the significance level p < 0.05. Test results: it was found that the teams examined the men and women of varied lack of or presence of pain disorders have similar average size basic morphological however, they differ in terms of used paddles and internship training. It analysis of the diversification of the results of the tests carried out clinical trials, for the most part does not show significant differences. Men without pain, however, is characterized by a significantly higher average test result Schober in the back. The diversity was found slightly more frequent differences structure interest teams fixed functional test results that indicate the trail of problems in the lumbar spine mobility players with pains, ailments. Among the men found them in the study of folds, and among the women in the study the hyperextension and slider on the right, and the results of numerical correlation Spearman test results and clinical internship training show little of their relationship and the total lack of statistical significance. Conclusions: The basic characteristics of the physical persons engaged in rowing are not factor significantly in the presence of back pain, which can, however, grow in the process of long-term training on the shore. Increased its frequency among players short paddles indicates the need for exercise, and among the contestants paddles long multidisciplinary action to restore the symmetry of the body. To reduce the function of the spine, and thus causing pain persons engaged in rowing in the increasingly determined by other factors related to the size and volume of loads and conditions for their implementation, as well as predisposed health and supporting biological renewal training.